Integridade superficial do aço-rápido AISI M3:2 após o processo de retificação - Vendrame, Saimon [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
High-Speed Steels are materials that exhibit high abrasive wear resistance coupled with relatively high toughness, properties that make them suitable for making cutting tools. Much of its properties are due to the presence of carbides in the microstructure. While these mechanical properties are favorable for use as tools, they impose challenges in their manufacture. The grinding process is employed in the final stages of the cutting tools manufacturing, such as taps and drills and the presence of carbides affects the efficiency of the grinding wheels. In this context, this work aims to investigate how the microstructure difference of class AISI M3: 2 steel, obtained from different suppliers, influences the grinding, taking into consideration the surface integrity. The materials, here named M-A, M-B, and M-C, were evaluated under three aspects: microstructure characteristics, abrasion resistance, and surface integrity after grinding. From the microstructure, carbides type MC and M6C were described regarding the shape and distribution, using for this purpose SEM and EDS. The abrasive wear resistance of the materials was measured using the pin-abrasive tribological test. After this characterization, flat tangential grinding tests were performed, using silicon carbide grinding wheel (SiC), in various work depths (between 10 μm and 30 μm). The ground samples surfaces were evaluated by measuring the roughness parameters, evaluated by SEM, and the microhardness profile near the surface was described. As a result, in the microstructure, the materials presented different morphologies and carbide distribution, and for the material, M-A presented the largest MC type vanadium carbides. The abrasive wear coefficient (k) for the three evaluated materials showed similar values (between 9.18 and 13.45 mm³.N-1.m-1), but the MA material presented abrasive wear instability (up to 28% variation between results). After grinding the surface of material M-C showed irregular scratches with material removal characteristics of fragile form. Was measured above-average microhardness (40% higher) in a layer up to 100 μm from the surface in the three materials sample in almost all conditions. These results are attributed to the effect of matrix brittleness and M6C carbides, which by fracturing result in fragile material removal.

Aços-rápidos são materiais que exibem elevada resistência ao desgaste abrasivo, aliada a uma tenacidade relativamente alta, propriedades estas que os tornam adequados para se fabricar ferramentas de corte. Grande parte de suas propriedades se deve a presença de carbonetos na microestrutura. Ao mesmo tempo que estas propriedades mecânicas são favoráveis para a utilização como ferramentas, tornam-se desafios na sua fabricação. O processo de retificação é empregado nas últimas etapas de fabricação de ferramentas de corte como machos e brocas e a presença dos carbonetos afetam a eficiência dos rebolos. Neste contexto, este trabalho visa investigar o quanto a diferença de microestrutura de aços-rápidos classe AISI M3:2, obtidos de diferentes fornecedores, influencia na retificação, levando em consideração a integridade superficial. Os materiais, aqui nomeados como M-A, M-B e M-C, foram avaliados sob três aspectos: características da microestrutura, resistência à abrasão e integridade da superfície após a retificação. Da microestrutura os carbonetos tipo MC e M6C, foram descritos quanto à forma e a distribuição, utilizando para isso MEV e EDS. A resistência à abrasão dos materiais foi medida recorrendo ao método de ensaio tribológico pino-lixa. Após esta caracterização, foram realizados ensaios de retificação tangencial plana com rebolo de Carboneto de Silício (SiC) em várias penetrações de trabalho (entre 10 µm e 30 µm). As superfícies das amostras foram avaliadas mensurando a rugosidade, avaliadas com MEV, e descrito o perfil de microdureza próximo a superfície. Como resultados, na microestrutura os materiais apresentaram diferentes morfologias e distribuição de carbonetos, sendo que para o material M-A apresentou os maiores carbonetos de vanádio tipo MC. O coeficiente de desgaste abrasivo (k) para os três materiais avaliados apresentaram valores próximos (entre 9,18 e 13,45 mm³.N-1.m-1), mas o material M-A, apresentou instabilidade no desgaste abrasivo (até 28% de variação entre os resultados). Após a retificação a superfície do material M-C apresentou riscos irregulares com características de remoção de material de forma frágil. Foram medidas microdureza acima da média (40% maiores) em uma camada de até 100 µm a partir da superfície nos três materiais. Atribui-se a esses resultados o efeito da fragilização da matriz e dos carbonetos tipo M6C, que por se fraturarem resultam em remoção de material de modo frágil.
Surface integrity assessment of AISI M3:2 high-speed steel after grinding
Keywords: Grinding; High-speed steels; Pin-abrasive test; Primary carbides; Abrasive wear; Retificação; Aço-rápido; Pino-lixa; Desgaste abrasivo; Carbonetos primários